Pembentukan bandar raya Melayu bestari (Kuala Lumpur Institut Perkembangan Minda, 1996)
Bandar raya Melayu bestari, Malaysian concept of city planning for Shah Alam and other cities in Selangor, Malaysia; papers of a meeting.
Includes index.
Keywords: City planning -- Malaysia -- Shah Alam (Selangor) -- Congresses; Urbanization -- Malaysia -- Selangor -- Congresses